Real Returns of Private Households with Different Financial Assets — A Comparison of Germany and Austria - Michael Andreasch; Marc Peter Radke; Manuel Rupprecht (Wirtschaftsdienst)
Abstract The paper discusses the real returns of German and Austrian households of different financial wealth groups in times of ultra-low interest rates. While returns decreased across all groups, the decline is rarely claimed, at least so far. Moreover, it is shown that — contrary to popular belief — rich households are particularly affected, although their returns today are still higher than those of the poor. While the general developments are similar, the yield level in Austria is consistently lower than in Germany. Overall, the asset structure is key for the results. Economic policy should therefore aim at a higher diversification of assets, especially for the poor, by effectively improving financial education.